Underwater cultural heritage facing maritime spatial planning: Legislative and technical issues. (1st November 2018) - Papageorgiou, Marilena
Abstract: Underwater Cultural Heritage (hereinafter UCH) constitutes an invaluable resource that has been poorly – if at all – addressed in most spatial planning attempts, due to the sectorial approach that has prevailed so far when planning in the sea. Lately however, that spatial planning in the marine space (MSP) is being re-launched under a place-based approach, the chances and challenges for UCH are considerably different. According to the existing international legislation (UNCLOS), coastal states can only interfere with UCH up to their Contiguous Zone (24 nm from the baseline), whilst beyond that limit UCH is left "abandoned" (unless "flag" or "cultural origin" states claim their protection). Of course, this "freezing" of jurisdictions beyond the CZ, means that for the greatest part of the oceans and seas, UCH protection totally depends on the wise regulation of all other human activities that affect directly or indirectly, cultural heritage. The paper argues that MSP under a place-based approach is a unique opportunity for better protection and wiser management of UCH in greater distances than ever, provided that coastal states proclaim their EEZ (in order to extend as much as possible the area within which they can practice MSP and therefore, tackle conflicts and encourage synergies with UCH). The paper proposes a five-step strategy for considering UCH in MSP. Step 1: Register and evaluate UCH sites and objects, Step 2: Identify ways to upgrade the economic value of UCH, Step 3: Select the most appropriate type of protection zoning, Step 4: Provide regulations and restrictions for activities within the UCH protection zone, Step 5: Ensure integration and cohesion of the planning adopted in the UCH buffer zones with the spatial/sea-use planning adopted in the wider marine area. The paper concludes by highlighting that beyond any strategy, the greater challenge and stake is how to compromise blue growth trend with UCH preservation and promotion. Highlights: According to UNCLOS, jurisdiction on UCH "freeze" beyond the Contiguous Zone; i.e. for the most part of oceans and seas. UCH management and protection greatly depends on MSP, to regulate human activities directly or indirectly affecting UCH. MSP under a place-based approach is a unique opportunity for wiser management and protection of UCH in greater distances than ever. In the future, the greatest challenge for UCH will be how to compromise blue growth with UCH preservation and promotion. Considering UCH in MSP necessitates: registration and evaluation; upgrade of economic value; selection of protection zone; implementation of planning; integration into the wider marine region.